Adhesion and Invasion of Gastric Mucosa Epithelial Cells by Helicobacter pylori - Huang, Ying; Wang, Qi-long; Cheng, Dan-dan; Xu, Wen-ting; Lu, Nong-hua (Frontiers in Cellular and Infection Microbiology, 2016)
Helicobacter pylori is the main pathogenic bacterium involved in chronic gastritis and peptic ulcer and a class 1 carcinogen in gastric cancer. Current research focuses on the pathogenicity of H. pylori and the mechanism by which it colonizes the gastric mucosa. An increasing number of in vivo and in vitro studies demonstrate that H. pylori can invade and proliferate in epithelial cells, suggesting that this process might play an important role in disease induction, immune escape and chronic infection. Therefore, to explore the process and mechanism of adhesion and invasion of gastric mucosa epithelial cells by H. pylori is particularly important. This review examines the relevant studies and describes evidence regarding the adhesion to and invasion of gastric mucosa epithelial cells by H. pylori.